The financial condition of Pampanga - Duran, Manuel Gerardo G. (Philippine Management Review, 2009)
The passage of the 1991 Local Government Code was a serious effort at strengthening the financial condition of local government units by providing them with greater revenue raising powers and by devolving many expenditure functions from the national government to local governments. The paper that follows will evaluate the financial condition of a typical high-growth province in the Philippines. It will analyze the factors that shape its financial performance and will determine whether, in recent years, the province has gained greater fiscal autonomy and has become more efficient at providing public goods and services needed for its development.